Managing salinity and waterlogging in the Indus Basin of Pakistan - Qureshi, Asad Sarwar; McCornick, Peter G.; Qadir, Manzoor; Aslam, Z. (2008)
Waterlogging and salinization are major impediment to the sustainability of irrigated lands and livelihoods of the farmers, especially the smallholders, in the affected areas of the Indus Basin. These problems are the result of a multitude of factors, including seepage from unlined earthen canals system, inadequate provision of surface and subsurface drainage, poor water management practices, insufficient water supplies and use of poor quality groundwater for irrigation. About 6.3 million ha are affected by different levels and types of salinity, out of which nearly half are under irrigated agriculture. Since the early 1960s, several efforts have been made to improve the management of salt-affected and waterlogged soils. These include lowering groundwater levels through deep tubewells, leaching of salts by excess irrigation, application of chemical amendments (e.g. gypsum, acids, organic matter), and the use of biological and physical methods. However, in spite of huge investments, the results have in general been disappointing and the problems of waterlogging and salinity persist. This paper reviews sources, causes and extent of salinity and waterlogging problems in the Indus Basin. Measures taken to overcome these problems over the last four decades are also discussed. The results reveal that the installed drainage systems were initially successful in lowering groundwater table and reducing salinity in affected areas. However, poor operation and maintenance of these systems and provision of inadequate facilities for the disposal of saline drainage effluent resulted in limited overall success. The paper suggests that to ensure the sustainability of irrigated agriculture in the Indus Basin, technical and financial support is needed and enhanced institutional arrangements including coordination among different federal and provincial government agencies to resolve inter-provincial water allocation and water related issues is required.